Health care reform in radiology - Semelka, Richard C.; Elias, Jorge, Jr. (Hoboken, New Jersey : Wiley Blackwell, 2013)
The first book-length treatment of this absolutely essential topic, Health Care Reform in Radiology provides a cogent, concise discussion of major issues related to health care reform from the perspective of fellow imaging specialists. This latest volume in the Current Clinical Imaging series provides radiologists with a solid footing in where they are now and where they can expect to be over the next ten years. Topics include: evidence-based outcomes for health care delivery, impact of imaging tests' effectiveness, patient safety, medicolegal reform, reimbursement issues, universal hea.
Health care reform : the scope of the problem / Richard C. Semelka, Diane Armao, and Jorge Elias Jr. -- Only studies which are necessary / Diane Armao, Jorge Elias Jr., and Richard C. Semelka -- Radiation dose reduction / Jorge Elias Jr. and Richard C. Semelka -- Alternate imaging studies to CT / Jorge Elias Jr., Lauren M.B. Burke, and Richard C. Semelka -- Patient information / Jorge Elias Jr. and Richard Semelka -- Are we doing the right study? / Diane Armao, Jorge Elias Jr., and Richard C. Semelka -- Radiology medical education / Jorge Elias Jr. and Richard C. Semelka -- Quality metrics for radiology practice / Richard C. Semelka and Jorge Elias Jr. -- Medicolegal reform / Jorge Elias Jr. and Richard C. Semelka -- Pressures on reduced compensation for clinical service / Jorge Elias Jr. and Richard C. Semelka -- National health care systems / Jorge Elias Jr., Lauren M.B. Burke, Richard C. Semelka -- Research in radiology / Richard C. Semelka [and five others].
Includes bibliographical references and index.
Online resource; title from PDF title page (Myilibrary, viewed on July 25, 2013).
Keywords: Radiology -- United States; Health care reform -- United States; Radiology -- economics; Radiology -- trends; Costs and Cost Analysis; Health Care Reform; Quality of Health Care; Unnecessary Procedures -- economics; MEDICAL -- Allied Health Services -- Radiological & Ultrasound Technology; MEDICAL -- Radiology & Nuclear Medicine; Health care reform; Radiology; United States; United States; Electronic books